James Coleman - Baker, George; Bellour, Raymond; Coleman, James (Cambridge, Mass. : MIT Press, 2003)
- James Coleman 1970-1985 (1985) / Anne Rorimer ##- The place of the spectator in the work of James Coleman (1983) ; The enigma of the hero in the work of James Coleman (1983) / Jean Fisher ##- The living dead (living and presumed dead) (1996) / Raymond Bellour ##- Narratives of no return: James Coleman's guaiRE (1993) / Luke Gibbons ##- Memory lessons and history tableaux: James Coleman's archaeology of spectacle (1995) / Benjamin H.D. Buchloh ##- A tempered agnosia (1992) / Lynne Cooke ##- Live vocals (2002) / Kaja Silverman ##- " ... and then turn away?" (1997) ; Reinventing the medium: introduction to Photograph (1999) / Rosalind Krauss.
boek
Keywords: Coleman, James